Genetic risk, parental history, and suicide attempts in a diverse sample of US adolescents - Barzilay, Ran; Visoki, Elina; Schultz, Laura M.; Warrier, Varun; Daskalakis, Nikolaos P.; Almasy, Laura (Frontiers in Psychiatry, 2022)
Background: Adolescent suicide is a major health problem in the US marked by a recent increase in Black/African American youth suicide trends. While genetic factors partly account for familial transmission of suicidal behavior, it is not clear whether polygenic risk scores of suicide attempt can contribute to suicide risk classification. Objectives: To evaluate the contribution of a polygenic risk score for suicide attempt (PRS-SA) in explaining variance in suicide attempt by early adolescence. Methods: We studied N=5,214 non-related youth of African and European genetic ancestry from the Adolescent Brain Cognitive Development (ABCD) Study (ages 8.9-13.8 years) who were evaluated between 2016 and 2021. Regression models tested associations between PRS-SA and parental history of suicide attempt/death with youth-reported suicide attempt. Covariates included age and sex. Results: Over three waves of assessments, 182 youth (3.5%) reported a past suicide attempt, with Black youth reporting significantly more suicide attempts than their White counterparts (6.1% vs 2.8%, P<.001). PRS-SA was associated with suicide attempt (odds ratio [OR]=1.3, 95% confidence interval [CI] 1.1-1.5, P=.001). Parental history of suicide attempt/death was also associated with youth suicide attempt (OR=3.1, 95%CI 2.0-4.7, P<.001). PRS-SA remained significantly associated with suicide attempt even when accounting for parental history (OR=1.29, 95%CI= 1.1-1.5, P=.002). In European ancestry youth (n=4,128), inclusion of PRS-SA in models containing parental history explained more variance in suicide attempt compared to models that included only parental history (∆R2=0.7%, P=0.009). Conclusions: Findings suggest that PRS-SA may be useful for youth suicide risk classification in addition to established risk factors.